Managerial Regret and Inventory Pricing - Li, Meng; Liu, Yan (Management Science, 2022)
In this paper, we study a regretful seller’s problem of selling a fixed number of goods over a finite and known time horizon. The seller engages in counterfactual thinking to compare her selected price with other forgone alternatives. If a forgone alternative (ex post) generates a better outcome than the selected one, then the seller experiences regret. We characterize the pricing decision of a regretful seller and find that, although regret leads the seller to set a price that is lower than that set by an unbiased seller, the regretful seller employs decision policies whose structure is similar to those of the unbiased seller: the price decreases with the remaining inventory and increases with the time-to-go. Interestingly, we find that the seller who has a greater number of goods does not necessarily receive greater revenue. This paper was accepted by Manel Baucells, behavioral economics and decision analysis.